Analysis of Determinants of QRIS Analysis of Determinants of QRIS Use in North Sumatra with the TAM Model (Technology Acceptance Model) - Afriza Ulfa Ritonga, Afriza Ulfa Ritonga; Rahmani, Nur Ahmadi Bi; Qarni, Waizul (Amkop Management Accounting Review (AMAR), 2025)
This study uses a quantitative approach to analyze the factors that influence the use of QRIS (Quick Response Code Indonesian Standard) in the North Sumatra region. The model used is the Technology Acceptance Model (TAM), which evaluates the influence of Perceived Ease of Use and Perceived Usefulness on Attitude Toward Using and Behavioral Intention to Use QRIS. Data was collected through surveys and analyzed using path analysis to test the relationship between variables. The results showed that Perceived Ease of Use affects Perceived Usefulness and user attitude, which in turn affects behavioral intention to use QRIS. These findings confirm that the TAM model is effective in explaining the adoption of digital payment technology in North Sumatra. However, uneven digital infrastructure and low technological literacy are still the main challenges in increasing widespread adoption of QRIS. This research recommends improving digital access and education as strategic steps.